Ghrelin alleviates biliary obstruction-induced chronic hepatic injury in rats - YEGEN, BERRAK; ERCAN, FERİHA (ELSEVIER, 2008)
Background: Reactive oxygen species and oxidative stress are implicated in hepatic stellate cell activation and liver fibrosis, which are initiated by recruitment of inflammatory cells and by activation of cytokines. Objective: The possible anti-oxidant and anti-inflammatory effects of ghrelin were evaluated in a hepatic fibrosis model in rats with bile duct ligation (BDL). Methods: Under anesthesia, bile ducts of Sprague Dawley rats were ligated, and half of the rats were subcutaneously administered with ghrelin (10 ng/kg/day) and the rest with saline for 28 days. Sham-operated control groups were administered saline or ghrelin. On the 28th day of the study, rats were decapitated and malondialdehyde (NIDA) content - an index of lipid peroxidation, and myeloperoxidase (MPO) activity - an index of neutrophil infiltration - were determined in the liver tissues. Oxidant-induced tissue fibrosis was determined by collagen contents, while the hepatic injury was analyzed microscopically. Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) levels and lactate dehydrogenase (LDH) levels were determined to assess liver function and tissue damage, respectively. Pro-inflammatory cytokines; TNF-alpha, IL-1 beta and IL-6 were also assayed in plasma samples. Results: In the saline-treated BDL group, hepatic NIDA levels, MPO activity and collagen content were increased (p < 0.001), suggesting oxidative organ damage, as confirmed histologically. In the ghrelin-treated BDL group, however, all of the oxidant responses were reversed significantly (p < 0.05-p < 0.001). Serum AST, ALT, LDH levels, and cytokines were elevated in the BDL group as compared to the control group, while this increase was significantly decreased by ghrelin treatment. Conclusion: Owing to the anti-inflammatory and anti-oxidant effect as demonstrated in our study, it is possible to speculate that exogenously administered ghrelin may possess an antifibrotic effect against biliary obstruction-induced liver fibrosis. Thus, it seems likely that ghrelin may be of potential therapeutic value in protecting the liver fibrosis and oxidative injury due to biliary obstruction. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: bile duct ligation; ghrelin; hepatic fibrosis; lipid peroxidation; PROINFLAMMATORY CYTOKINES; ACYLATED PEPTIDE; ACTIVATION; FIBROSIS; MYELOPEROXIDASE; ANGIOGENESIS; CIRRHOSIS; DAMAGE